A partially buckling-restrained brace with T-shaped double core for seismic retrofit: Experimental study, numerical analysis, and local stability design. (1st February 2023) - Zeng, Cong; Zhang, Yifei; Zhao, Junxian; Xu, Guoshan; Wang, Dehong; Pan, Tianlin
Highlights: Partially BRB with T-shaped double core (PTBRB) is proposed for seismic retrofit. Cyclic tests conducted to examine seismic performance and failure modes of PTBRB. Numerical analysis performed to identify the controlled buckling mode of PTBRB. Theoretical local buckling capacity of PTBRB derived to achieve seismic fuse function. Abstract: A novel partially buckling-restrained brace with T-shaped double core (PTBRB) was proposed for the seismic retrofit of existing T-shaped steel members consisting of two separated steel angles. The retrofitting scheme primarily comprises two external steel angles and one cover plate which are bolted to serve as restrainer to prevent global buckling of existing T-shaped steel members. Cyclic tests were performed to verify the effectiveness of the retrofitting scheme and evaluate the PTBRB performance as seismic fuse. The results showed that adoption of the retrofitting scheme had negligible influence on the elastic stiffness of the T-shaped steel members, but their axial compression force capacity was increased by 60 %. The PTBRB specimens exhibited full hysteresis before failure, with the best ductility coefficient and cumulative plastic deformation capacity of 11.83 and 523, respectively. The controlled buckling mode of the PTBRB was identified by numerical analysis, and the results showed that the local buckling of a single steel angle member was responsible for the stiffness degradation of the PTBRB hysteresis. Theoretical local stability analysis of PTBRB was carried out according to Bleich's theory and Lundquist's theory and the test results confirm that the Bleich's theory is more reliable for predicting the theoretical inelastic critical load. The maximum compression capacity of the PTBRB corresponding to the local stability requirement of a single steel angle member is proposed to achieve the seismic fuse function, which is further validated by numerical analysis.